Salivary duct carcinoma: Prospective multicenter study of 61 cases of the Réseau d'Expertise Français des Cancers ORL Rares. Issue 3 (13th November 2018) - Villepelet, Aude; Lefèvre, Marine; Verillaud, Benjamin; Janot, François; Garrel, Renaud; Vergez, Sébastien; Bertolus, Chloé; Malard, Olivier; de Gabory, Ludovic; Mauvais, Olivier; Baujat, Bertrand; ,
Abstract: Background: The purposes of this study were to describe the characteristics of a prospective multicenter series of patients with salivary duct carcinoma and to investigate prognostic factors. Methods: Patients included for salivary duct carcinoma between 2009 and 2016 in the Réseau d'Expertise Français des Cancers ORL Rares (REFCOR) database were selected. Immunohistochemical analyses were performed. Results: Sixty‐one patients were included in this study. The primary site was the parotid gland in 90% of the cases. Fifty‐seven percent of the tumors were stage IV, 65% of patients had lymph node involvement, and 10% had metastases. Tumors showed androgen receptor (89%) and human epidermal growth factor receptor 2 (HER2)/neu (36%). Ninety‐four percent of patients underwent surgery and 86% had postoperative radiotherapy. Six patients were treated with targeted therapies. The 3‐year overall survival (OS) was 74% and the 3‐year disease‐free survival (DFS) was 44%. Tumor stages III to IV reduced DFS (hazard ratio [HR] 4.3; P = .04). The N2/3 class reduced distant metastasis‐free survival (HR 7.3; P = .007). Conclusion: Salivary duct carcinoma prognosis is poor and is correlated with tumor stage and lymph node classification. Androgen receptor and HER2/neu should be tested as they offer the possibility of targeted therapies.